2020
DOI: 10.21037/atm.2019.12.109
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic changes and potential regulatory mechanism of intrauterine human chorionic gonadotropin co-cultured with peripheral blood mononuclear cells infusion in mice with embryonic implantation dysfunction

Abstract: Background: This study aimed to explore whether intrauterine infusion of peripheral blood mononuclear cells (PBMCs) could induce favorable transcriptomic changes in the endometrium for embryo implantation and the potential mechanism.Methods: Twenty-one mice were randomly divided to five groups, including a normal pregnancy (NP) group, an embryo implantation dysfunction (EID) group, an EID with human chorionic gonadotropin (hCG) group, an EID with PBMCs group, and an EID with hCG co-cultured with PBMCs group. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…As a derivative of this amino acid, SLC16A1 is important for fetal and placental development, and its expression was decreased upon hyperosmotic stress [53]. SLC15A2 expression was down regulated in EID (embryo implantation dysfunction) mice, and this gene might be useful to repair an injury after an intrauterine perfusion treatment [54]. Our GO enrichment analysis showed that the mRNA expression of transport-related genes including SLC24A3, SLC22A2, SLC38A3, SLC52A3, SLC15A1, SLC16A6, SLC43A2, SLC9A1, SLC7A4, SLC3A1, and SLC16A1 were up regulated, but that of other transport-related genes including SLC28A2, SLC6A12, SLC15A2, SLC7A2, and SLC26A8 were down regulated under HS.…”
Section: Discussionmentioning
confidence: 99%
“…As a derivative of this amino acid, SLC16A1 is important for fetal and placental development, and its expression was decreased upon hyperosmotic stress [53]. SLC15A2 expression was down regulated in EID (embryo implantation dysfunction) mice, and this gene might be useful to repair an injury after an intrauterine perfusion treatment [54]. Our GO enrichment analysis showed that the mRNA expression of transport-related genes including SLC24A3, SLC22A2, SLC38A3, SLC52A3, SLC15A1, SLC16A6, SLC43A2, SLC9A1, SLC7A4, SLC3A1, and SLC16A1 were up regulated, but that of other transport-related genes including SLC28A2, SLC6A12, SLC15A2, SLC7A2, and SLC26A8 were down regulated under HS.…”
Section: Discussionmentioning
confidence: 99%